A study on the tribological behavior of hybrid and all-steel rough sliding contacts. (March 2023) - Long, Weishan; Chen, Zhixiong; Li, Zhixiong; Królczyk, Grzegorz; Shi, Yijun
Hybrid bearing is a kind of bearing that uses ceramic materials instead of steel and other metal materials as rolling elements. It is often used to reduce (i.e., rolling or sliding) friction resistance. Although many published works have shown that hybrid bearings are more effective than ordinary bearings in reducing friction resistance, improving service life, and reducing the occurrence of bearing failure, many few works have been focused on the tribological properties of hybrid bearings only under sliding friction conditions. Therefore, it is crucial to understand the tribological behavior of the bearing materials to evaluate the sliding tribological process. In this paper, the tribological properties of silicon nitride-bearing steel friction pair (Si3 N4 -GCr15 pair) and bearing steel-bearing steel friction pair (GCr15-GCr15 pair) under oil lubrication were experimentally studied. An optical three-dimensional (3D) reconstruction method was used to investigate the microscopic and 3D morphologies of the friction pairs during the wear evolution process. The results show that the changing trends of the micrograph, 3D topography, friction coefficient, and surface roughness are consistent. A wear failure evaluation model was built based on the data extracted from the worn surface morphology. The model indicated that the friction performance of the Si3 N4 -GCr15 pair is better than that of the GCr15-GCr15 pair. The mechanism of friction performance of different friction pairs under lubrication conditions is studied, which provides good reference for the design of subsequent hybrid bearings.